Determination of Antibacterial and Wound Healing Potentials of Ethanolic Extract of Cydonia oblonga Miller Fruit - Dilshad Najeeb, Venus; Moffaq Abdulaziz , Sazan; Tofiq Kurtas , Prshng (Diyala Journal of Medicine, 2020)
Background: Cydonia oblonga Miller (Quince) is one of the oldest cultural plants that belongs to the Rosaceae family. The bioactive components of Quince fruit are thought to have antimicrobial properties and able to accelerate the process of wound healing. The active ingredients that have antibacterial activity such as polyphenols can overcome the resistant mechanisms of bacteria and enhance killing through disturbing their metabolic activities. Objective: To determination of antibacterial and wound healing potentials of ethanolic extract of Cydonia oblonga Miller Fruit. Patients and Methods: The extract was prepared using hydroalcoholic extraction of quince whole fruit. Predominant wound bacteria isolates were obtained from active wounds on oral cheek mucosa of Albino Rabbits in a pilot study in which swab samples were taken from the induced oral wounds on the 2nd day and immediately sent to the lab. The specimens were cultured on bacteriological media under aerobic and CO2 conditions at 37°C for 24hr. discrete colonies were identified using microscopy, cultural characteristics and biochemical examinations. Different concentrations of the extract (15, 30, 60, 90 and 120mg/ml) using well-diffusion agar method were tested for their antibacterial activity. In another pilot study, the effective extract concentration on wound healing was determined after 3, 5, 7 days post wounding. The extract concentration showed the best healing activity was used later and compared with normal healing (without treatment) and chlorhexidine-treated wounds. Histological assessment were used to judge on healing activity. Results: Twelve bacterial isolates belonging to Neisseria sp., Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli were tested. On the whole, all the isolates showed sensitivity to quince extract especially at high extract concentrations. Quince extract 60mg/ml oral irrigation showed significant antibacterial effect following 3 days post wounding as no bacterial colonies were detected in the test group when compared with the negative and positive control groups with sever inflammatory infiltrate in all groups. Nearly, complete healing of the wounds after 5 and 7 days was recorded in all groups. Conclusion: Cydonia oblonga Miller fruit ethanolic extract could be regarded as a good antibacterial substance with broad spectrum activity that promotes wound healing as well. The best concentration for both was 60mg/ml.